Dynamics of Newton's functions of Barna's polynomials - Piyapong Niamsup (International Journal of Mathematics and Mathematical Sciences)
We define Barna's polynomials as real polynomials with all real roots of which at least four are distinct. In this paper, we study the dynamics of Newton's functions of such polynomials. We also give the upper and lower bounds of the Hausdorff dimension of exceptional sets of these Newton's functions.